Formulation and Evaluation of the Wound Healing Chitosan Gel of Povidone Iodine - Mishra, Ashwani (International Journal of Pharmaceutical & Biological Archive, 2014)
Formulation and Evaluation of the Wound Healing Chitosan Gel of Povidone Iodine